The song of songs and the fashioning of identity in early Latin christianity - Shuve, Karl (Oxford, United Kingdom Oxford University Press, 2016)
Cover -- The Song of Songs and the Fashioning of Identity in Early Latin Christianity -- Copyright -- Dedication -- Preface -- Contents -- Abbreviations -- PERIODICALS AND SERIES -- ANCIENT SOURCES -- Introduction -- 0.1. ESOTERICISM AND EROS: THE SHAPE OF MODERN SCHOLARSHIP ON THE INTERPRETIVE TRADITION -- 0.2. THE ARGUMENT AND SCOPE OF THE BOOK -- Part I: The Song of Songs in North Africa and Spain -- 1: "A Garden Enclosed, a Fountain Sealed": The Church as Closed Community in Cyprian and the Donatists -- 1.1. CYPRIAN OF CARTHAGE AND THE PROBLEM OF REBAPTISM
1.1.1. Persecution and the Rebaptism Crisis -- 1.1.2. The Problem of Rebaptism and the Song of Songs -- 1.1.3. The Song of Songs in Cyprian's Letters and De unitate -- 1.1.4. The Legacy of Cyprian -- 1.2. THE DONATIST SCHISM -- 1.2.1. The Origins of the Donatist Schism -- 1.2.2. Optatus' Against Parmenian the Donatist -- 1.2.3. Traces of Donatist Use of the Song in the Writings of Augustine -- 2: "As a Lily among the Thorns": The Church as Mixed Community in Pacian, Tyconius, and Augustine -- 2.1. PACIAN OF BARCELONA AND THE NOVATIANS IN SPAIN -- 2.1.1. Pacian's Career
2.1.2. The Correspondence with Simpronian -- 2.1.3. The Song of Songs in Pacian's Writings -- 2.2. TYCONIUS AND THE BIPARTITE CHURCH -- 2.2.1. Identifying Tyconius -- 2.2.2. Tyconius' Use of the Song of Songs -- 2.2.3. The Sources of Tyconius' Exegesis -- 2.3. AUGUSTINE OF HIPPO AND THE HIDDEN JUDGMENT OF GOD -- 2.3.1. Nuptial Theology in Augustine's Thought -- 2.3.2. The Song of Songs in Anti-Manichean Polemic -- 2.3.3. De Baptismo: The Song, Ritual Purity, and the Corpus Permixtum -- 3: "The Church is the Flesh of Christ": The Tractatus de Epithalamio of Gregory of Elvira
3.1. THE EARLIEST LATIN COMMENTARIES: VICTORINUS OF POETOVIO AND RETICIUS OF AUTUN -- 3.1.1. Victorinus as Commentator and Translator -- 3.1.2. Reticius' Lost Commentary on the Song -- 3.2. THE DATE, SETTING, AND STRUCTURE OF THE TRACTATUS -- 3.2.1. Textual Considerations -- 3.2.2. The Setting of its Composition and Revision -- 3.3. FROM INCARNATION TO FINAL JUDGMENT: THE SONG OF SONGS AS HISTORY OF THE CHURCH -- 3.3.1. The Incarnation and the Origins of the Church -- 3.3.2. The Church's Struggles with "Heretics" -- 3.3.3. Crucifixion, Resurrection, and the Kingdom of God -- 3.4. CONCLUSION
Part II: The Song of Songs in Italy -- 4: "Like the Holy Church, Unsullied by Intercourse": Ambrose, Virgins, and the Song -- 4.1. WESTERN CONTROVERSY AND EASTERN INFLUENCE -- 4.1.1. The Influence of Athanasius -- 4.1.2. The Politics of Asceticism -- 4.2. DE VIRGINIBUS: VIRGINITY AND THE ANGELIC LIFE -- 4.2.1. Virginity and/as Martyrdom -- 4.2.2. The Symbolic Significance of Virginity -- 4.2.3. The Song's Bride as Consecrated Virgin -- 4.3. DE VIRGINITATE: FROM VIRGIN BODIES TO VIRGIN SOULS -- 4.3.1. Situating the De Virginitate -- 4.3.2. The Formation of the Virgin Soul
4.3.3. Towards an Ascetic Vision of Christian Identity
Includes bibliographical references and indexes
Online-Ausg.
Keywords: Bible -- Criticism, interpretation, etc; Church History -- Primitive and early church, ca. 30-600; Bible ; Song of Solomon ; Criticism, interpretation, etc ; History ; Early church, ca. 30-600; Electronic books